Mononuclear zinc(II) Schiff base complexes as catalysts for the ring-opening polymerization of lactide. (5th January 2020) - Fuchs, Martin; Schmitz, Sebastian; Schäfer, Pascal M.; Secker, Tim; Metz, Angela; Ksiazkiewicz, Agnieszka N.; Pich, Andrij; Kögerler, Paul; Monakhov, Kirill Yu.; Herres-Pawlis, Sonja
Graphical abstract: Highlights: Four new Schiff base zinc complexes are reported. All complexes show high activity in the ring-opening polymerization of lactide under industrial conditions. In situ Raman monitoring in melt reveals semi-logarithmic behavior of the polymerization. The polymerization rate constant reaches almost the speed of SnOct2 . MALDI-ToF analysis shows the ligand and co-initiator as end-group. Abstract: Materials combining bio-based resource and degradability aspects such as polylactide (PLA) can represent a sustainable alternative to commercially used oil-based plastics. With tin octanoate (Sn(Oct)2 ) as the catalyst of choice for industrial scale PLA production, traces of the toxic heavy metal can be released into the environment, rendering PLA unsuitable for specific applications. Herein we present four new homoleptic zinc Schiff base complexes that offer facile synthesis and can be handled under aerobic conditions. These robust, tetra-coordinated complexes have been tested as catalysts for the ring-opening polymerization (ROP) of lactide and are well suited under industrially relevant conditions. In situ Raman spectroscopy has been used to determine the apparent reaction rate constant ( k app ) for all complexes at 150 °C in bulk . For the fastest complex a k p of 3.66 ± 0.14 × 10 –2 L mol −1 s −1 was additionally determined. For this catalyst, 71% conversion and a number-averaged molar mass of above 90000 g mol −1 has been reached within less than 30 min at a monomer-to-initiator ratio ([M]/[I]) of 1000:1. The good polydispersity ( Ð = 1.7) indicates a controllable ROP via the coordination-insertion mechanism (CIM).